THE ROLE OF THE TEACHER IN FORMING EDUCATION OF CHARACTER AND MORAL CHILDREN - Siti Hafsoh; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
This paper is a scientific idea that aims to provide an overview of the importance of the teacher's role in shaping the education of children with character and morals through the ongoing process of learning in schools carried out by an educator. Here it is emphasized that the task of the teacher to students at school is not only to give lessons, but the real teacher is a teacher who is able to educate and be a good example to his students. Therefore the importance of the role of teachers in shaping the education of children with character and morals. The method used in this writing is literature research. The purpose of this paper is to remind the importance of the role of teachers in shaping children's education with character and morals.